An evaluation of Emergency Management of Severe Burn (EMSB) course in Bangladesh: a strategic direction. Issue 1 (25th April 2017) - Biswas, Animesh; Rahman, Fazlur; Maitz, Peter; Baset, Kamran Ul; Hossain, Jahangir; Mashreky, Saidur Rahman
Abstract: Background: Burn is one of the major public health problems in Bangladesh. Specialized personnel and technologies are required, however, in many cases they are not readily available. Taking the situation into account, Interplast Australia and New Zealand, Australia & New Zealand Burn Association (ANZBA), and Centre for Injury Prevention and Research, Bangladesh (CIPRB) initiated Emergency Management of Severe Burn (EMSB) training programme for Bangladeshi physicians in 2008 to help improving their burn management skill. The study was designed to evaluate the effect of EMSB programme in Bangladesh. Methods: Both qualitative and quantitative methods were adopted. A cross-sectional survey was conducted to obtain quantitative information from 38 randomly selected EMSB-trained doctors among 380 trained physicians based on a five year database of EMSB (2008-2012). In-depth interviews (IDIs) and focus group discussion (FGD) were used as data collection techniques to get information. Results: A total of 32 participants completed the interview. It was found that 87.5% ( n =28) doctors were using their skill in burn management that they learnt from the EMSB course. About 43.8% ( n =14) doctors felt that the course largely helped improve their confidence. Majority (56.2%, n =18) of doctors stated EMSB is essential for the Bangladeshi doctors to learn better management of burns. Qualitative findings show that the courses were organized successfully with an excellent coordination, maintaining same quality and standard as running anywhere in the world. For its effectiveness, the course has been recommended to train graduate nurses and junior doctors from the periphery of the country. Conclusions: EMSB has already created a large doctor community who are able to effectively manage burn patients. It also has proven its indispensability for learning burn management skill. The EMSB established a platform to serve the burn victims and reduce the burden of injuries in Bangladesh.